The Effect of Digital Psychoeducation and ICU Delirium Care Bundle Programmes on Nurses' Competency, Confidence and Care‐Related Strain: A Systematic Review and Narrative Synthesis - Baraa I. Aldayyat; Ekhlas Al Gamal; Jafar A. Alshraideh; Rabia H. Haddad (Nursing in Critical Care, 2026)
ABSTRACT Background Delirium is a common and serious complication among critically ill patients, affecting approximately 20%–80% of ICU populations and contributing to increased mortality, prolonged mechanical ventilation, extended hospital stays, cognitive impairment and higher healthcare costs. Nurses play a central role in delirium prevention, assessment and management; however, deficiencies in delirium‐related knowledge, confidence and assessment practices remain widespread. Digital psychoeducation and delirium care bundle interventions have been increasingly implemented to address these gaps. Aim To systematically review and narratively synthesize evidence regarding the effects of digital psychoeducation and ICU delirium care bundle programmes on nurses' competency, confidence and care‐related strain. Study Design A systematic review with narrative synthesis was conducted in accordance with PRISMA 2020 and SWiM guidance. Six electronic databases (PubMed, CINAHL, Scopus, Web of Science, Embase and ProQuest) were searched. Eligible studies included quasi‐experimental, pre–post and quality‐improvement studies evaluating delirium‐focused educational or care bundle interventions among ICU nurses. Methodological quality was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Quasi‐Experimental Studies. Results Eight studies involving approximately 472 nurses from five countries met the inclusion criteria. Competency outcomes improved in 87.5% of studies, with delirium knowledge increasing by 100%–150%, CAM‐ICU assessment accuracy reaching 95.5%, documentation completeness exceeding 91% and bundle compliance reaching 97.5%. Confidence improved across all studies evaluating this outcome, with increases ranging from 35.3 to 60.1 percentage points, including one study reporting a very large effect size (Cohen's d = 2.31). The only study assessing care‐related strain demonstrated a 48.8% reduction in delirium‐related nursing stress. Overall, educational interventions were associated with improved clinical practice indicators, although implementation varied across healthcare settings. Conclusion Digital psychoeducation and ICU delirium care bundle programmes consistently improve nurses' delirium‐related competency and confidence and may reduce care‐related strain. However, evidence regarding strain remains limited, and variability in clinical implementation highlights the need for more rigorous controlled studies and long‐term evaluations to strengthen the evidence base. Relevance to Clinical Practice Integrating digital delirium education programmes and structured care bundles into ICU nursing practice can improve nurses' competency, confidence and adherence to evidence‐based delirium assessment, supporting earlier recognition and higher quality patient care. Trial Registration CRD4201380975